Polycomb epigenetic mechanisms: role of PcG complexes - Pirrotta, Vincenzo (Henry Stewart Talks, 2007)
Polycomb mechanisms, PcG complexes, PRC1 complex, PRC2 complex, A Drosophila PRE, PcG complexes and CpG islands, recruitment of PRC2, Dynamic activities of PcG complexes
Updated at 2017/12/31